Wind electric prime mover using air passing from vehicles in highway - Wong Khing Pauh (Universiti Malaysia Perlis, 2009)
This project is to generate power from the wind created by the vehicles on highway. That is used turbines generate power from the wind created by the vehicles that drive past them in opposite directions. This concept is engine moves the car, the car moves the air, the air moves the turbines. The highway wind is the inadvertent result of energy expenditure and it would be a pretty passive collection process. Wind is simply air in motion. It is caused by the uneven heating of the earth's surface by the sun. Wind energy is used to produce electricity. Wind is called a renewable energy source because we will never run out of it. The objectives of this project is study and research the possible of turn the highways into wind farm, to study and develop a type of system that can be used to generate energy from wind created by the vehicles on highways, to study a feasible wind turbine and the efficiency of energy conversion and obtain a DC voltage that is enough to charge a battery. A gear system was developed in this project to increase rotation of the generator shaft. Beside that, a rechargeable battery is used to charge the energy from the output generator and power electronic such as voltage regulator also study in this project.